A Review on Ultra- and Nanofiltration/Diafiltration Processes of the Food-Oriented Agro-industrial - ., Aspiyanto; Susilowati, Agustine; Melanie, Hakiki; Maryati, Yati; Mulyani, Hani; Budiari, Setyani (International Journal of Membrane Science and Technology, 2023)
This review was conducted to implement the potential use of ultra- and nanofiltration as a separation technique accompanied by a diafiltration (DF) technique. We start by introducing the principle of pressure-driven membrane-based separation process and DF process in general, and selected applications of ultra- and nanofiltration/diafiltration techniques on the food-oriented agro-industrial products in particular, such as nanofiltration/diafiltration (NF/DF) technique of mung beans autolysate, ultrafiltration/diafiltration (UF/DF) technique of forest honey products, and ultrafiltration/diafiltration (UF/DF) technique of fish gelatin. We also describe the potential benefits as green and sustainable and the drawbacks of membrane-based separation process. Both relevant information and data related to this review were obtained from various sources originating from international organizations (FAO and UNEP, United States Standards for Grades of Extracted Honey, USA and National Honey Board (NHB), USA), review of various scientific articles and scientific literature, handbook, and the selected result of experiment activity. We hope this review manuscript is useful for further research into membrane technology implementations in food-oriented agro-industrial products and in a wider range of applications.